Evaluation of combined gene regulatory elements for transcriptional targeting of suicide gene expression to malignant melanoma - Rothfels, Heike; Paschen, Annette; Schadendorf, Dirk (Experimental dermatology, 2003)
Abstract: Selective killing of tumors can be achieved by targeting the transcription of suicide genes via specific DNA control elements to malignant cells. Three different enhancer-promoter systems were constructed and evaluated for their capability to direct gene expression to melanoma. Two tissue-specific (tyrosinase and MIA) promoters and one weak viral promoter were fused to multiple tandem copies of a melanocyte-specific enhancer element. Reporter gene assays revealed a maximum increase in transcription by combining each promoter with 3-4 copies of the enhancer and demonstrated that all enhancer-promoter combinations exhibited tissue-specific activity. Though this activity was still significantly less than that of the strong but unspecific cytomegalo virus (CMV) promoter. In contrast, when these combinations were employed to drive the expression of two suicide genes, encoding the diphtheria toxin A chain (DT-A) and the prodrug-activating herpes simplex virus thymidine kinase (TK), respectively, only those constructs in which transcription was under the control of tissue-specific promoter elements mediated selective killing of melanoma cells. This killing was in the range of cell death induced by CMV promoter activity. Our data indicate that the enhancer/tyrosinase and enhancer/MIA promoter constructs but not the viral promoter constructs can provide a valuable tool for selective suicide gene expression in melanoma.
Gesehen am 25.11.2020